Perception of Kinesiology and Physiotherapy students on the quality of the virtual classroom - Almirón, Marcos; Morales, Lelis; Vázquez, Mercedes; Delgado, Lourdes; Gómez, Leonor; Lang, Nancy; Dos Santos, Claudia and (Medicina Clínica y Social, 2021)
Introduction: The COVID-19 pandemic has caused teaching in higher education institutions around the world to drastically change from physical to virtual mode. Objective: To know the perception of Kinesiology and Physiotherapy students in Paraguay about the quality of the virtual classroom in the context of the COVID-19 pandemic. Methodology: observational, exploratory, descriptive, cross-sectional, prospective study, with non-probability sampling, of consecutive cases. An online instrument was shared through social networks and messaging applications, in order to study sociodemographic and socioeconomic characteristics, as well as those related to educational quality. For the latter, the “Cuestionario de Evaluación de la Calidad de los cursos virtuales de Educación Social, Calidad General del Entorno y de la Metodología Didáctica” by Santoveña Casal was used. Results: 331 students participated in the research. 74.62% were female with a mean age of 23.06±4.9. 93.35% used the virtual classroom for the first time. Regarding the quality of the virtual classroom, 45.62% of the participants stated that “some” attention is paid to the teaching-learning process and 47.43% mentioned that it is “somewhat” effective and efficient. 32.63% of the participants responded that “very little” is compensated for the economic investment with the quality of the course. Conclusion: Today there is a new task in the teaching work, and where elements of virtuality have begun to be used with the aim of not slowing down the teaching-learning processes. Our research shows that most of the participants have used a virtual classroom for the first time during this pandemic and, in addition, it allows us to have a preliminary reading on the quality of it in these complex times.